Land use changes in the region of Dravinjske gorice - Žiberna, Igor; Jöbstl, Gita; Pucko, Klemen; Žagavec, Aljaž (Journal for Geography, 2022)
Land use changes in the region of Dravinjske goriceThe article analyses the changes in land use in the area of the Dravinjske Gorice in the period 2000–2022. Changes in land use are shown depending on the selected natural geographical elements and by cadastral municipalities. The directions of land use change in the considered period and the coefficient of extensification are also analysed. In the past, viticulture was one of the agricultural activities that gave the identity of this region, so for the probe area "Škalce-Bezina-Tepanje" we analysed the changes in the viticulture areas in terms of relative heights, global radiation and viticulture ratings in time profiles 1824–2000–2022.